Omics Analysis Reveals the Mechanism of Enhanced Recombinant Protein Production Under Simulated Microgravity - Huangfu, Jie; Kim, Hye Su; Xu, Ke; Ning, Xiaoyu; Qin, Lei; Li, Jun; Li, Chun (Frontiers in Bioengineering and Biotechnology, 2020)
Simulated microgravity (SMG) is regarded as a suitable environment to produce recombinant proteins. This study showed β-glucuronidase expressing Escherichia coli had higher productivity of recombinant protein and higher plasmid copy number under SMG compared with the normal gravity condition. The cellular changes was analyzed at both transcriptomic and proteomic levels. The up-regulation of a group of ribosome/RNA polymerase genes and a cluster of genes involving energy metabolism at transcriptomic level stood out for improved production of recombinant protein under SMG. The protein folding modulators such as chaperones were up-regulated at proteomic level, which could be a result of the increased activity of protein synthesis and can help recombinant protein production. Protein export was also strengthened revealed at both transcriptomic and proteomic levels. The results demonstrated that SMG is a favorable environment for recombinant protein production arousing the up-regulation of protein synthesis, protein folding and protein export.